DAMPAK MIGRASI SIRKULER TERHADAP DESA ASAL MIGRAN - Sunarto Hs (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1991)
This researchwas conductedvin two villages at Gunung Kidul Regency. The aim was to identify the complexity of circular migrations and their remittances such as migrants self-esteem, reason for migration, selection of places of destination, economic activity and their earnings, remittances, and the impacts of remittances on their places of origin. The findings of this research: all remittances (money, goods, knowledge, experience, skills, and ideas) had positive impacts on the village environment and incultivatingland. The village society had a positive perceptionon the circular migration, which eventually had been internalized.